A Study of Students’ Awareness Level of Professional Accounting Ethics Based on Q.S. Al-Baqarah (2): 282–284 - Khotami, Hanifa Nurul; Khairunisa, Irma; Bahri, Jamiludin Saepul; Aisah, Nur; billa, Salsa; Kusumaning Daru, Ulya Khairunnisa; Suresman, Edi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Professional ethics in the accounting profession are crucial for accountants in managing financial matters to prevent unethical actions in the preparation and presentation of financial statements. However, in practice, many accountants still violate professional ethics due to individual materialistic motives, which are not in accordance with Islamic provisions and sharia principles. Therefore, this study aims to determine the level of awareness among Accounting students based on Islamic values as contained in Q.S. Al-Baqarah (2): 282–284 and the hadith of the Prophet Muhammad (peace be upon him), which are derived from the Al-Qur'an. The research method used is descriptive statistics with a quantitative approach to examine the level of students’ awareness of accounting professional ethics based on Islamic sharia, using a closed-ended questionnaire as the instrument. The instrument testing results indicate that the data are valid and reliable. Statistical results show that students have a high level of awareness of professional ethics. This provides empirical evidence that the inclusion of ethical content in accounting education significantly influences the moral development of students.